Tensile properties of duplex UNS S32205 and lean duplex UNS S32304 steels and the influence of short duration 475 ºC aging - Sérgio Souto Maior Tavares; Juan Manuel Pardal; Hamilton Ferreira Gomes de Abreu; Cristiana dos Santos Nunes; Manoel Ribeiro da Silva (Materials Research, 2012)
Duplex stainless steels are high strength and corrosion resistant steels extensively used in the petrochemical and chemical industries. The aging at 475 ºC for long periods of time provokes embrittlement and deterioration of corrosion resistance. However, short duration aging at 475 ºC may be used as heat treatment to improve mechanical resistance with small decrease in the other properties. In this work the flow stress curves of lean duplex UNS S32304 and duplex UNS S32205 steels were modeled with Hollomon's equation and work hardening exponents (n) were determined. The analyses were conducted in specimens annealed and heat treated at 475 ºC for short periods of time. The aging at 475 ºC for 4 hours, 8 hours and 12 hours promoted significant hardening with small decrease of ductility. The work hardening exponents of both steels were compared, being higher in the duplex steel than in the lean duplex grade.